Recruitment and retention of women in fishing communities in HIV prevention research - Ssetaala, Ali (Pan Afr Med J, 2015)
INTRODUCTION: Women in fishing communities in Uganda are more at risk and have higher rates of HIV infection. Socio-cultural gender norms, limited access to health information and services, economic disempowerment, sexual abuse and their biological susceptibility make women more at risk of infection. There is need to design interventions that cater for women's vulnerability. We explore factors affecting recruitment and retention of women from fishing communities in HIV prevention research. METHODS: An HIV incidence cohort screened 2074 volunteers (1057 men and 1017 women) aged 13-49 years from 5 fishing communities along Lake Victoria using demographic, medical history, risk behaviour assessment questionnaires.1000 HIV negative high risk volunteers were enrolled and followed every 6 months for 18 months. Factors associated with completion of study visits among women were analyzed using multivariable logistic regression. RESULTS: Women constituted 1,017(49%) of those screened, and 449(45%) of those enrolled with a median (IQR) age of 27 (22-33) years. Main reasons for non-enrolment were HIV infection (33.9%) and reported low risk behaviour (37.5%). A total of 382 (74%) women and 332 (69%) men completed all follow up visits. Older women (>24 yrs) and those unemployed, who had lived in the community for 5 years or more, were more likely to complete all study visits. CONCLUSION: Women had better retention rates than men at 18 months. Strategies for recruiting and retaining younger women and those who have stayed for less than 5 years need to be developed for improved retention of women in fishing communities in HIV prevention and research Programs.